154k views
4 votes
Find the term that must be added to the equation X 2- 6r = 7 to make it into a perfect square.

Find the term that must be added to the equation X 2- 6r = 7 to make it into a perfect-example-1

1 Answer

3 votes

In this problem, we have to complete the square for a quadratic equation.

Recall that a perfect square trinomial comes in the form:


a^2+2ab+b^2

Sometimes, we have to create that form by using the following method to complete the square:

1. Get the equation equal to


ax^2+bx=-c

2. Divide the b-term and square it:


((b)/(2))^2

3. Add that new value to both sides of the equation:


ax^2+bx+((b)/(2))^2=-c+((b)/(2))^2

It looks really confusing in this format, so let's follow our equation to get a better idea.

We are given:


x^2-6x=7

Luckily, we already have it in the format required for Step 1. So we can complete Step 2 by identifying the b-value.


\begin{gathered} x^2-6x=7 \\ \\ \text{ The b-value is:}b=-6 \end{gathered}

So, we have:


((-6)/(2))^\rightarrow(-3)^(^2)\rightarrow9

Finally for Step 3, we add that 9 to both sides to get:


\begin{gathered} x^2-6x+9=7+9 \\ \\ x^2-6x+9=16 \end{gathered}

The term tha tmust be added to the equation to make it into a perfect square is 9.

User Skyrocker
by
5.6k points